Simpanan Karbon pada Padang Lamun di Perairan Pulau Poteran Madura Jawa Timur - Wita Kristianty Sirait; Retno Hartati; Widianingsih Widianingsih (Universitas Bangka Belitung, 2022)
Blue carbon is a carbon stored in the coastal ecosystem such as mangrove ecosystems, seagrass beds and brackish/salty swamps. Seagrass ecosystems can absorb and drain large amounts of carbon from the atmosphere and deposited to tissues or sediments for a long time. The aim of this study was to determine the type, percentage of seagrass cover and carbon stocks in seagrass beds on Poteran Waters. The study was conducted in January - March 2019. Sampling was done by purposive sampling method. Carbon deposit in seagrasses was calculated using the loss on ignition (LOI) method. Seagrass species found on Poteran Island were 7 species, namely Enhalus acoroides, Thalassia hemprichii, Cymodocea serrulata, Cymodocea rotundata and Halodule uninervis, Halophila ovalis and Syringodium isoetifolium. Cymodocea serrulata had the highest density value with value 336 ind/m2 and the highest seagrass cover value was 20.45% by Cymodocea rotundata. The value of biomass under the substrate (4.24 dw.m-2 - 400.5 dw.m-2) is more than the value of biomass on the substrate (2.43 dw.m-2 - 54.52 dw.m-2). Carbon values under the substrate (1.52 gC.m-2 - 141.09 gC.m-2) and above the substrate (0.71 gC.m-2 - 5.83 gC.m-2). The carbon value in the two station was not normally distributed but did not have a significant carbon comparison value using the Mann Whitney U-Test analysis test.